2020
DOI: 10.1007/s12325-020-01362-6
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib and Subsequent Therapy for Radioactive Iodine-Refractory Differentiated Thyroid Cancer: A Real-World Study of Clinical Effectiveness in the United States

Abstract: Introduction: Lenvatinib has become the most commonly prescribed first-line (1L) agent for the treatment of radioactive iodine-refractory differentiated thyroid cancer (RAI-r DTC) since its approval in 2015. With no real-world studies describing clinical outcomes of 1L lenvatinib and subsequent therapy, the current study aimed to assess treatment sequencing and related clinical outcomes in patients treated with 1L lenvatinib in the USA Methods: We conducted a multisite, retrospective chart review of US patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
(25 reference statements)
4
16
0
1
Order By: Relevance
“…In our study the surgical intervention was addressed in 10 patients and systemic therapy with tyrosine kinase inhibitors (TKI) was addressed for 5 patients, 2 of them also having the BRAF mutation present. In fact, the evaluation of genetic mutations is applicable in the process of development of therapies targeting the production pathway [ 17 , 18 , 19 ]. In some studies, a better response rate to treatment has been observed in BARF+ patients, leading to the development of studies only for this category of patients [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study the surgical intervention was addressed in 10 patients and systemic therapy with tyrosine kinase inhibitors (TKI) was addressed for 5 patients, 2 of them also having the BRAF mutation present. In fact, the evaluation of genetic mutations is applicable in the process of development of therapies targeting the production pathway [ 17 , 18 , 19 ]. In some studies, a better response rate to treatment has been observed in BARF+ patients, leading to the development of studies only for this category of patients [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of Real-World Studies (RWS) showed that treatment with lenvatinib, sorafenib and pazopanib, followed or accompanied by another therapy, may improve the clinical outcome (i.e., higher PFS) of patients with RAIR-DTC [ 123 , 124 , 125 ]. However, the observed AEs, most frequently fatigue, asthenia and hypertension (HT), forced to reduce the MKI dose.…”
Section: Currently Used and Investigated Targeted Therapies In Tcsmentioning
confidence: 99%
“…The existence of tumor-related symptoms can affect patients’ performance status (PS). Most patients enrolled in the large pivotal clinical trials had an Eastern Cooperative Oncology Group (ECOG) PS of 0–1 [ 20 , 24 ], whereas 7.7–15% of the patients had an ECOG PS ≥ 2 in the real-world data of lenvatinib for RR-DTC from several countries [ 91 , 92 ]. ECOG PS (0 vs. ≥1) was a prognostic factor for PFS (HR 0.51, 95% CI 0.34–0.76, p = 0.0008) and OS (HR 0.44, 95% CI 0.27–0.73, p = 0.001) in a post hoc analysis of the SELECT trial [ 50 ].…”
Section: Possible Indications For Starting Mkismentioning
confidence: 99%